Analysis of Factors That Influence Employees Turnover Intention (Study of Starred Hotel Employees in North Sulawesi) - Tamengkel, Lucky; Rumawas, Wehelmina (JURNAL ADMINISTRASI BISNIS (JAB), 2020)
Turnover intention is an early sign of employee turnover. For the hotel industry, turnover problems will certainly affect the performance of the company/hotel, and will certainly have an impact on the tourism sector. This study aims to analyze the influence of work stress factors, organizational commitment, and job satisfaction on the employee's turnover intention. This research uses a survey method with a quantitative descriptive approach. The population in this study were all-star hotel employees in North Sulawesi. The research sample was taken by an area random sampling technique. The questionnaire was used to obtain data from 159 respondents. Data were collected and analyzed using Structural Equation Modeling (SEM) techniques, with the help of Amos 24 software. The results showed that job stress had a positive and not significant effect on job satisfaction, work stress had a positive and significant effect on employee turnover intentions, job stress had a negative and not significant effect on organizational commitment, job satisfaction had a negative and not significant effect on employee turnover intentions, and commitment organizational and not significant positive effect on employee turnover intentions.